AB1067 Eighteen cases of crowned dens syndrome: Presentation and diagnosis. (23rd January 2014) - Godfrin-Valnet, M.; Wendling, D.; Godfrin, G.; Godard, J.; Prati, C.; Toussirot, E.; Michel, F.
Abstract : Background: Eighteen cases of crowned dens syndrome: presentation and diagnosis. Objectives: To etablish the clinical, biological and radiological criteria of crowned dens syndrome, a little known etiology of acute neck pain. Methods: We carried out a retrospective observational study of patients who were treated in our department between 1990 and 2011. Results: Eighteen cases were recorded. Most of the patients affected (61%) were women, aged over 60 on average (median 75, 5 years). Clinically, the diagnostic triad (neck pain, stiff neck and headaches) was present in 13 out of 18 cases. From a biological point of view, a marked inflammatory syndrome was observed in over half the cases (11 out of 17.64%) with a mean CRP levels of 82.3 mg/l (23 - 275) at admission. Laboratory tests should look for any underlying metabolic disease, especially in patients aged under 50. In our study, the cervical bone CT scan confirmed the suspected diagnosis in 100% of cases. In 44% of cases, calcifications were located on the transverse ligament of the atlas and the alar ligament, in 16.6% calcifications were mottled, and located at the posterolateral surface of the dens. Other imaging tests provided little information, including standard radiographs of the cervical spine. MRI is not able to make a specific diagnosis, but enables us to eliminate differential diagnoses. The numerous differential diagnoses that often lead to additional and unnecessary therapeutic tests are a major problem in crowned dens syndrome. In our study, in over half of the cases, other diagnoses were initially considered, such as: infectious cervical spondylodiscitis, impingement, Horton's disease, polymyalgia rheumatica. Infectious etiologies, spinal inflammatory diseases or other types of inflammatory vasculitis may lead to mistakes due to the stiff neck pain triggered. The standard treatment is based on anti-inflammatory drugs (NSAIDs, colchicine) or corticosteroids. In our series, treatment with colchicines was used as the first-line treatment in 77.7%of cases. These treatments are highly effective: a spectacular recovery ad integrum of cervical mobility may be observed within 48 hours. Conclusions: Crowned dens syndrome should be known to other medical specialties because it can be cause diagnostic mistake. A comprehensive consultation, a complete clinical examination and a precise analysis of the imaging will avoid unnecessary tests an treatment. References: Dirheimer Y, Wackenheim A. Crowned odontoid apophysis. Apropos of the development mechanism of certain images of axis manifestations. Sem Hop 1974; 50: 2077-80. Disclosure of Interest: None Declared